Counter-Terrorism in the Nusantara National Capital City: A PPRR-Based Analysis of Cyber, Maritime, and Social Vulnerabilities - Aulya Nanda Permana (Pusat Studi Politik dan Kebijakan Strategis Indonesia (POLKASI), 2026)
This study examines terrorism threats in the Nusantara National Capital City through the PPRR framework, namely prevention, preparation, response, and recovery, to identify key vulnerabilities and formulate an integrated counter-terrorism strategy. The article argues that terrorism in the new capital should not be understood merely as the possibility of physical attacks on the center of government, but as a multidimensional threat shaped by social vulnerabilities, land and governance issues, digital dependence arising from smart city development, and cross-border maritime exposure. Drawing on a descriptive qualitative design based on literature review and secondary data, the study shows that the security challenges of the Nusantara National Capital City are closely linked to local social grievances, cyber risks targeting Internet of Things-based critical infrastructure, and maritime-terrorism risks associated with the Sulu-Sulawesi corridor. The analysis further finds that effective counterterrorism in the Nusantara National Capital City cannot be pursued through sectoral measures alone, but requires the integration of pentahelix-based deradicalization, cyber resilience centered on local CSIRT and national BSSN coordination, and strengthened maritime defense through patrols, UAVs, and surveillance of strategic sea routes. It concludes that the security of the new capital will be more robust if cyber, maritime, and social threats are treated not as separate policy problems, but as mutually connected layers within a sustainable national security design.